2014
DOI: 10.1186/1556-276x-9-570
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of uniform 4H-SiC mesopores by pulsed electrochemical etching

Abstract: In this letter, the uniform 4H silicon carbide (SiC) mesopores was fabricated by pulsed electrochemical etching method. The length of the mesopores is about 19 μm with a diameter of about 19 nm. The introduction of pause time (Toff) is crucial to form the uniform 4H-SiC mesopores. The pore diameter will not change if etching goes with Toff. The hole concentration decreasing at the pore tips during the Toff is the main reason for uniformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Therefore, the anodic etching process of SiC can be summarized as following: SiC is first oxidized into SiO 2 and CO 2 by taking the holes provided by the electrical bias and then SiO 2 is dissolved by HF.SiC+2normalH2O+normalH2normalO2+6normalh+SiO2+CO2+6normalH+SiO2+4HFnormalH2SiF6+2normalH2O…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the anodic etching process of SiC can be summarized as following: SiC is first oxidized into SiO 2 and CO 2 by taking the holes provided by the electrical bias and then SiO 2 is dissolved by HF.SiC+2normalH2O+normalH2normalO2+6normalh+SiO2+CO2+6normalH+SiO2+4HFnormalH2SiF6+2normalH2O…”
Section: Resultsmentioning
confidence: 99%
“…Finally, electrical field is frequently used for wet etching as an electrochemical circuit can directly provide holes required by oxidation. As the holes provided by the electrical bias is intrinsically uniformly distributed, only porous SiC can be obtained by anodic etching . So far, fabricating SiC nanowires, which is the foundation to build 3D devices, by wet etching methods has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies presented in references [18,19], it has been demonstrated that the addition of H 2 O 2 helps to enhance the oxide formation rate.…”
Section: Electrochemical Etchingmentioning
confidence: 93%
“…Silicon carbide has become a new option for improving power applications due to its characteristics of higher voltage operating at thinner active layers, extended power density, higher frequency switching, better heat dissipation, smaller system size and lower system cost [1,2]. In the past few years, commercial SiC rectifiers and MOSFETs have been rated at 1.2-1.7 kV.…”
Section: Introductionmentioning
confidence: 99%